2022
DOI: 10.1089/aut.2021.0077
|View full text |Cite
|
Sign up to set email alerts
|

“The Languages That You Know Draw the Boundary of Your World”: A Thematic Analysis of the Experiences of Autistic Bilingual Adults Living in the United Kingdom

Abstract: S. (2022). "The languages that you know draw the boundary of your world": A thematic analysis of the experiences of autistic bilingual adults living in the UK. Autism in Adulthood.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The issue is particularly pertinent because family language decisions can be the source of much parental stress and anxiety (Sevinç 2022), even though bilingualism may positively influence children's well-being (Müller et al 2020). Indeed, for those who choose to raise their autistic child in a multilingual environment, benefits may include enriched relationships with family and community members (Digard et al 2023;Yu 2016), participation in religious and cultural life (Howard et al 2019a;Jegatheesan 2011;Sher et al 2022), and, in adulthood, more social and vocational opportunities (Digard et al 2022). Recent research also suggests that language learning is a particular passion or strength for some autistic adults (Caldwell-Harris 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The issue is particularly pertinent because family language decisions can be the source of much parental stress and anxiety (Sevinç 2022), even though bilingualism may positively influence children's well-being (Müller et al 2020). Indeed, for those who choose to raise their autistic child in a multilingual environment, benefits may include enriched relationships with family and community members (Digard et al 2023;Yu 2016), participation in religious and cultural life (Howard et al 2019a;Jegatheesan 2011;Sher et al 2022), and, in adulthood, more social and vocational opportunities (Digard et al 2022). Recent research also suggests that language learning is a particular passion or strength for some autistic adults (Caldwell-Harris 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, parents of children on the autism spectrum have frequently reported receiving advice from practitioners to prioritize one language in their interactions with their child (Fernandez y Garcia et al, 2012;Kremer-Sadlik, 2005). Studies that gathered data from multilingual autistic adults found that they often reflected positively on their multilingualism and the impact on their lives (e.g., Digard et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Research also suggests some tentative positive effects on cognition including facets of executive function skills [e.g., (11)(12)(13)] and crucially, in lived experiences. Specifically, parents describe increased familial connections and closeness when they are able to express themselves in their first language [e.g., (3,14)] and autistic bilingual adults have expressed the benefits of bilingualism on domains such as widening access to work and social opportunities, social interactions, and self-understanding (15,16).…”
Section: Introductionmentioning
confidence: 99%